1983
DOI: 10.1007/bf01208267
|View full text |Cite
|
Sign up to set email alerts
|

Some remarks on BRS transformations, anomalies and the cohomology of the Lie algebra of the group of gauge transformations

Abstract: We show that ghosts in gauge theories can be interpreted as Maurer-Cartan forms in the infinite dimensional group ^ of gauge transformations. We examine the cohomology of the Lie algebra of ^ and identify the coboundary operator with the BRS operator. We describe the anomalous terms encountered in the renormalization of gauge theories (triangle anomalies) as elements of these cohomology groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
151
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(152 citation statements)
references
References 20 publications
1
151
0
Order By: Relevance
“…The anomalies associated to a linearly realised group are well known, and are classified by symmetric Casimirs. A nice way to derive such anomalies is by means of the 'Russian formula' [36][37][38][39] 29) to derive a (d + δ k )-cocycle from any symmetric Casimirs by use of the Cartan homotopy formula. In four dimensions, the relevant Casimir is the symmetric tensor of rank three, and the Cartan homotopy formula gives…”
Section: Jhep12(2010)052mentioning
confidence: 99%
“…The anomalies associated to a linearly realised group are well known, and are classified by symmetric Casimirs. A nice way to derive such anomalies is by means of the 'Russian formula' [36][37][38][39] 29) to derive a (d + δ k )-cocycle from any symmetric Casimirs by use of the Cartan homotopy formula. In four dimensions, the relevant Casimir is the symmetric tensor of rank three, and the Cartan homotopy formula gives…”
Section: Jhep12(2010)052mentioning
confidence: 99%
“…This explains why the definition of these general transformations requires to introduce the ghost field. In fact, in Bonora & Cotta-Ramusino (1983), it was shown that the ghost field can be identified with the Maurer-Cartan form of the gauge group G , that is to say with the form η ∈ Lie(G ) * ⊗ Lie(G ) that satisfies η(ξ) = ξ, ∀ξ ∈ Lie(G ). This means that the ghost η is a Lie(G )-valued 1-form dual to Lie(G ).…”
Section: Brst Symmetrymentioning
confidence: 99%
“…Instead of attaching a copy V x of the vector space V to each point x ∈ M , we now attach the space R x of all bases s in V x . The structure group G rotates the bases in R x by means of the free and transitive right action R x × G → R x , with (s, g) → s ′ = s · g. 9 We will now characterize the kind of objects that the spaces R x are. If a basis s 0 (x) in a fiber R x is arbitrarily chosen, an isomorphism ϕ s 0 (x) between R x and the structure group G is induced.…”
Section: Rigid Fiber Bundlesmentioning
confidence: 99%
See 1 more Smart Citation
“…An useful and powerful method to find the non-trivial solutions of Eq. (1) is given by the descent-equations technique [5,6,7,8,9,10,11,12,13,14]. Writing ∆ = A Eq.…”
Section: Introductionmentioning
confidence: 99%